HUBUNGAN TEKNIK MENYUSUI DENGAN PROSES INVOLUSI UTERUS PADA IBU POST PARTUM FISIOLOGIS 0-14 HARI DI TPMB “S” CILINCING - Hidayati, Nurul; Siswati, Eny; Masyayih, Warda Anil; Novia, Deti (PRIMA WIYATA HEALTH, 2025)
Background: Uterine involution or uterine contraction is a process in which the uterus returns to its pre-pregnancy state. Uterine involution can also be said to be the process of returning the uterus to its original state or pre-pregnancy state. Objectives: The purpose of the study was to analyze the relationship between breastfeeding techniques and the process of uterine involution in post-partum physiological mothers 0-14 days at TPMB "S" Cilincing, North Jakarta. Methods: In this study, the author used a cross-sectional research design. The population in this study was all postpartum mothers with a uterine involution process as many as 30 respondents with a total sampling technique. The independent variables in this study are the investigation technique and the dependent variables in this study are the involution process, data collection techniques using observation sheets, data processing by editing, coding, scoring, and tabulating. Data analysis used the chi-square test with a significance of 0.01. Results: Data analysis using the Chi-Square test with a value of a = 0.01 From that postpartum mothers who did not properly carry out breastfeeding techniques mostly experienced slow involution, namely 7 people or 63.6%. Breastfeeding techniques that are done properly will increase uterine involution. The results of the chi-square test were obtained p= 0.001 < α = 0.05 and it can be interpreted that H1 is accepted, this study concludes that there is a Relationship between Breastfeeding Techniques and the Uterine Involution Process in Post-Partum 0-14 at TPMB "S" Cilincing North Jakarta.   Conclusion: It is hoped that health workers can approach the family to provide counseling guidance and motivation to postpartum mothers about the uterine involution process.